Governance and Public Health Decision-Making During the COVID-19 Pandemic: A Scoping Review - Sumegha Asthana; Sanjana Mukherjee; Alexandra L. Phelan; Claire J. Standley; Claire J. Standley (Frontiers Media S.A., 2024)
Objective: We provide an in-depth understanding of how governance and decision-making during the COVID-19 pandemic has been empirically characterized in the literature to identify gaps in research and highlight areas that require further inquiry.Methods: We searched peer-reviewed publications using empirical data published between Jan 1, 2020 and Jan 31, 2022 in three electronic databases to examine the process of governance and decision-making during the COVID-19 pandemic. Two authors independently screened the records and 24 publications were extracted for the review.Results: Governance is analyzed by its level at national, sub-national, community and by its aspects of process, determinants and performance. While different methodological approaches are used, governance is conceptualized in four ways 1) characteristics and elements, 2) leadership, 3) application of power and 4) models or arrangements of governance.Conclusion: For future pandemic preparedness, there is a need for more empirical research using a unified conceptual approach to governance, which integrates decision-making processes and can guide governance structures and mechanisms across different countries and contexts. We call for more inclusivity in who performs the research on governance and where.